Life cycle oriented low-carbon operation models of machinery manufacturing industry. (15th March 2015) - Du, Yanbin; Yi, Qian; Li, Congbo; Liao, Lan
Abstract: It is urgent for machinery manufacturing industry to implement low-carbon manufacturing to solve the problems of high-energy consumption and high-carbon emissions. Combining the theory of product life cycle, a system framework of low-carbon operation models in machinery manufacturing industry is established, which consists of an objective layer, a strategy layer, a process layer and a supporting layer. In addition, four typical low-carbon operation models of machinery manufacturing industry are proposed from the perspectives of low-carbon product design, source control, process control and EOL (end-of-life) product disposal respectively. Finally, the proposed models are illustrated in a case of implementing low-carbon manufacturing by a machine tool manufacturer.